Private Capital, Public Goods: Forest Plantations' Investment in Local Infrastructure and Social Services in Rural Tanzania - Mohammed B. Degnet; Edwin van der Werf; Verina Ingram; Justus Wesseler (Center for Economic Studies and ifo Institute (CESifo), 2017)
With the rapid expansion of private forest plantations worldwide, their impacts on local development are under scrutiny by NGOs and researchers alike. This study investigates the impacts of private forest plantations on local infrastructure and social services in rural Tanzania. We take a comparative approach involving households living in villages adjacent to private forest plantations and households in villages adjacent to a state-owned plantation. We use survey data from 338 households to analyze their perceptions about the impacts of the plantations on the number and quality of roads, bridges, and health centers, as well as on school enrolment and quality of education. We triangulate the results from a logistic regression model with observations of the size and quality of infrastructure and social services in the villages and with findings from focus group discussions. The results show that the private forest plantations have positively affected local infrastructure and social services in adjacent villages. The results suggest that large-scale private forest plantations can contribute to rural development in developing countries. We highlight the importance of taking into account the perceptions of various groups in society when assessing the sustainability of forestry investments and their impacts on local communities.
Keywords: H41; M14; Q01; Q15; Q23; 330; private forest plantations; infrastructure; public goods; perceptions; socio-economic impacts; Tanzania